Current Behaviour and Dynamics of the Lowermost Italian Glacier (Montasio Occidentale, Julian Alps). Issue 1 (29th October 2012) - Carturan, Luca; Baldassi, Giovanni A.; Bondesan, Aldino; Calligaro, Simone; Carton, Alberto; Cazorzi, Federico; Dalla Fontana, Giancarlo; Francese, Roberto; Guarnieri, Alberto; Milan, Nicola; Moro, Daniele; Tarolli, Paolo
Abstract Smaller glaciers (<0.5 km2) react quickly to environmental changes and typically show a large scatter in their individual response. Accounting for these ice bodies is essential for assessing regional glacier change, given their high number and contribution to the total loss of glacier area in mountain regions. However, studying small glaciers using traditional techniques may be difficult or not feasible, and assessing their current activity and dynamics may be problematic. In this paper, we present an integrated approach for characterizing the current behaviour of a small, avalanche‐fed glacier at low altitude in the Italian Alps, combining geomorphological, geophysical and high‐resolution geodetic surveying with a terrestrial laser scanner. The glacier is still active and shows a detectable mass transfer from the accumulation area to the lower ablation area, which is covered by a thick debris mantle. The glacier owes its existence to the local topo‐climatic conditions, ensured by high rock walls which enhance accumulation by delivering avalanche snow and reduce ablation by providing topographic shading and regulating the debris budget of the glacier catchment. In the last several years the glacier has displayed peculiar behaviour compared with most glaciers of the European Alps, being close to equilibrium conditions in spite of warm ablation seasons. Proportionally small relative changes have also occurred since the Little Ice Age maximum. Compared with the majority of other Alpine glaciers, we infer for this glacier a lower sensitivity to air temperature and a higher sensitivity to precipitation, associated with important feedback from increasing debris cover during unfavourable periods.